Improving self-efficacy for hearing aid self-management: the early delivery of a multimedia-based education programme in first-time hearing aid users. (2nd April 2020) - Gomez, Rachel; Ferguson, Melanie
Abstract: Objectives: This study examined the effect of a multimedia educational programme for first-time hearing aid users (C2Hear reusable learning objects, RLOs), delivered at the hearing assessment on (1) self-efficacy for hearing aids (primary outcome), and (2) readiness for hearing rehabilitation and hearing aid knowledge (secondary outcomes). Design: A single-centre, prospective, pre-post, randomised controlled trial with two arms. The intervention group ( n = 24) received RLOs, and the waitlist control group ( n = 23) received a printed booklet on hearing aids. Outcomes were measured at the hearing assessment and hearing aid fitting appointments. Study sample: Fifty-six adult first-time hearing aid users attending a publicly funded audiology service. Results: The RLO group showed significantly greater improvement in self-efficacy and knowledge of hearing aids than the control group. A borderline effect of readiness for hearing rehabilitation was also found. Potential links between hearing aid self-efficacy and knowledge were identified. Conclusions: Early delivery of the RLOs results in greater hearing aid self-efficacy and knowledge at the hearing aid fitting appointment, with indications that RLOs increase readiness for hearing rehabilitation. As knowledge, self-efficacy and readiness are cornerstones of self-management, the C2Hear RLOs can prime first-time hearing aid users to better self-manage their hearing aids before they receive them.